Augmented reality applications as a digital learning innovation in response to the pandemic - Batool, Hira (Frontiers in Education, 2022)
Augmented reality applications are digital learning innovations that can rapidly improve the learning of college and university students in the virtual setting. Ever since the beginning of the pandemic, on-site teaching has been pushed back to limit the spread of disease. This paper examines the attitudes and subjective and behavioral norms of 100 college students in Thailand toward digital learning innovations accessed through augmented reality applications. The study offers a theoretical model established through the theory of planned behavior (TPB) and uses it to investigate students’ choices of augmented reality applications as digital learning innovations in their courses. The data were analyzed through structural equation modeling. The findings showed that students’ acceptance of digital learning innovations through augmented reality applications could be explained through TPB wherever attitudinal and subjective factors showed significant influence; meanwhile, perceived behavioral control did not demonstrate a significant influence on college students. The findings acknowledge the positive effects of augmented reality applications as experienced by college students in Thailand.